Karakterisasi Karakter Agronomi Tomat (Lycopersixum esculentum Mill.) Hasil Introduksi untuk Perakitan Tomat Berdaya Hasil Tinggi - Putri, Dirgahani; Ade Sumiahadi; Yukarie Ayu Wulandari; Rosdiana; Sularno; Helfi Gustia; Ridwan Diaguna; Yeni Nurazizah; Paldi Saputra (Jurnal Agrosains dan Teknologi, 2025)
The increase in yields in tomato cultivation in Indonesia is due to the limited availability of superior varieties that can grow well and produce high production and quality. An effective method to increase tomato yield and quality is through the development of new tomato plant cultivars. Plant introduction is a process of moving plants from one area to another. Plant introduction is a process of moving plants from one area to another. This study aims to study the agronomic characteristics of four tomato plant varieties. This research was conducted at the experimental field of the Faculty of Agriculture, Muhammadiyah University of Jakarta, from June to December 2023. Research using two introduced tomato plant varieties and two commercial national tomato varieties as a comparison of the introduced tomato varieties is expected to be an additional genetic diversity and tomato plant varieties that can be used as ready-to-distribute varieties or genetic sources for tomato plant breeding programs. The results of the study showed that in general the two introduced genotypes had qualitative characteristics that were different from the two comparison varieties. In quantitative characters, the introduced genotypes TI01 and TI02 showed the same growth as the two comparison varieties, while in production characters they were significantly lower than the two comparison varieties.